Review of Phil Powrie and Robynn Stilwell, eds. 2006. Changing Tunes: The Use of Pre-existing Music in Film. Ashgate Popular and Folk Music Series. Aldershot, UK, and Burlington, VT: Ashgate Publishing - Biancorosso, Giorgio (Current Musicology, 2007)
This twelve-essay anthology brings together a diverse group of scholars-musicologists, film scholars, media and communication scholars, literature and area specialists- around one topic: the use of “pre-existnig music” in film. Through the anthology is somewhat inconsistent in quality and type of contribution, its appearance is welcome, for it provides not only the most extensive treatment of the subject to date but also the most convincing proof of the topic’s significance and intrinsically interdisciplinary, collaborative nature. The book is divided into two sections: “Pre-existing Classical Film Scores” and “Popular Music and Film”. The term “scores” in the heading of the first section suggests that it deals only with classical music used nondiegetically; in fact, both sections touch on diegetic and nondiegetic uses of repertories.